The contribution of producer co-operatives to economic development in the Limpopo Province - Nevhutalu, Lusani (My University, 2004)
Refer to document
Thesis (M. Dev.) -- University of the North, 2004
Keywords: Worker co-operatives; Economic development; Producer cooperatives -- South Africa -- Limpopo; Economic development -- South Africa -- Limpopo; Cooperative societies -- South Africa -- Limpopo